Separatism in Belgium: Key Factors Governing Walloon-Flemish Discrepancies - Egor A. Sergeev (Сравнительная политика, 2024)
The study is devoted to a retrospective analysis of separatism in Belgium and its development given the existing ethnic conflict between Flemish and Walloons. The research depicts the historical and contemporary dynamics of the problem. The aim of the study is to identify major factors that contributed to aggravation of the ethnic conflict and institutionalization of separatism, as well as influenced the further transformation of the separatist discourse in the country. To achieve this goal, the author uses an interdisciplinary approach with the use of historic, political science and economic categories and methods. The methodological basis of the work is formed by modern theoretical views on the types and causes of separatist sentiments, as well as options and strategies for dealing with the problem. The study relies on qualitative historical methods, it also uses statistical analysis, data from sociological surveys, and analyzes a wide range of documents, including the programs of political parties. One might argue that the evolution of ethnic separatism in Belgium was influenced by the following factors: linguistic division (as a fundamental precondition of the conflict), the factor of elites (which determined the main vector of the separatist discourse), the external factor (which contributed to the formation of Flemish separatism), the economic factor (which gave an impetus to the institutionalization of the country's division) and the ‘institutional’ factor itself. The latter is understood as the formation of ethnic groups in the country that are actually isolated from one another at the expense of the development of a full-fledged system of regional and community institutions. This factor seems to be extremely important, as it contributed to the ‘freezing’ of the ethnic conflict and at the same time incorporated a large number of imbalances associated with ethnic division into the system of consociational democracy. As a result, the stabilization of the conflict was achieved at the expense of destabilizing the central government in the country. In the modern political system of Belgium, the separatist discourse is widely instrumentalized. The ideas of dividing the country and reforming the state structure are gradually losing their impetus due to the emergence of new problems (migration, economic crisis, anti-establishment sentiments) and changing priorities of the right- wing political forces.